Efeitos da fotobiomodulação, do exercício e da lesão muscular num modelo experimental de recuperação alimentar pós desnutrição em ratos - Pezolato, Vitor Alexandre (2019)
Protein malnutrition has negative short- and long-term effects on the functioning of the most varied tissues. In this way, the present study focused on the evaluation of the biochemical, tissue and nutritional parameters, adaptive capacity and maintenance of aerobic training loads, metabolic response to physical exercise, muscular tensile strength, being these characteristics associated or not with the laser therapy, both in animals that underwent the process of protein malnutrition and nutritional recovery, as in animals that were fed a normoprotein diet. For this purpose, Wistar rats, weaned on the 21st day of life, were randomly divided into 10 groups, so-called: control (C), trained control (CT), trained and injured control (CTL), trained and irradiated control (CTLa), trained and irradiated trained control (CTLLa), recovered malnourished (DR) trained recovered malnourished (DRT), recovered and injured malnourished (DRTL), trained and irradiated recovered malnourished (DRTLa), trained injured and irradiated recovered malnourished (DRTLLa). Statistical analysis was performed by the Shapiro-Wilk normality test, followed by intra and intra-group comparisons, for which two-way ANOVA was used for multiple comparisons, followed by the Sidak test for parametric data, for non-parametric data the Kruskal-Wallis test was performed followed by the Dunn test, considering the critical value of p <0.05 for statistical significance. The condition of protein malnutrition when delineated in the early and critical stages of development may lead to changes in biological markers, which can be recovered with the normoprotein diet, but as deformation of muscle tissue, cardiac electrical conduction and blood parameters may not be recovered. Still, the photobiomodulation seems to favor the energetic condition in the physical exercise, such as improving muscular tensile strength and increasing glycogen reserves and may be a good instrument to be used for performance improvement, as well as for injury prevention and recovery.